Electric Tunable Structures Based on BaZrxTi1–x O3 and BaSnxTi1–xO3 Solid Solutions for Microwave Applications - A. V. Tumarkin; E. N. Sapego; A. G. Gagarin; N. V. Mukhin (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. An experimental study of the structural and electrophysical properties of multicomponent films of solid solutions of barium titanate-zirconate and barium titanate-stannate on sapphire substrates has been carried out. These materials are an alternative to the more studied barium-strontium titanate for use in microwave technology, due to the relatively high controllability. In this paper, it is shown that when using post-post high-temperature annealing, films with a component composition close to the composition of the sprayed targets are formed on the substrate. Optimal deposition temperatures of thin films of barium titanate-zirconate and barium titanate-stannate have been determined to obtain the best electrophysical parameters.Aim. Investigation of structural and microwave properties of BaZrxTi1-xO3 (BZT) and BaSnxTi1–xO3 (BSnT) films on dielectric substrates. These ferroelectric materials are promising in terms of losses and nonlinearity, and the formation of planar structures based on these materials on a dielectric substrate allows for a significantly higher level of operating power of the microwave device.Materials and methods. The crystal structure and phase composition of the obtained films were studied by X-ray diffraction using a DRON-6 diffractometer on the emission spectral line CuKa1 (λ = 1.5406 Å). Capacitance C and Q-factor (Q = 1/tg δ) of capacitors were measured at frequencies of 1 and 3 GHz using a resonator and an HP 8719C vector analyzer.Results. It is established that high-temperature annealing after film deposition has a significant effect on the crystal structure, phase composition of films and their electrical characteristics. For the first time, a low level of dielectric losses of planar capacitive elements based on titanate-stannate and barium titanate-zirconate films in the frequency range of 1…60 GHz with acceptable controllability has been demonstrated.Conclusion. The results obtained indicate the prospects of using thin ferroelectric films of BaSn0.5Ti0.5O3 and BaZr0.5Ti0.5O3 solid solutions in microwave devices.